Uranium(IV) Thio‐ and Selenoether Complexes: Syntheses, Structures, and Computational Investigation of U−ER2 Interactions. Issue 1 (7th December 2021) - Gray, Novan A. G.; Price, Jeffrey S.; Emslie, David J. H.
Abstract: Rigid thioether‐ and selenoether‐containing pincer proligands H[AS2 Ph 2 ] (1 ) and H[ASe2 Ph 2 ] (2 ) were synthesized, and deprotonation provided the potassium salts [K(AS2 Ph 2 )(dme)] (3 ) and [K(ASe2 Ph 2 )(dme)2 ] (4 ). Reaction of two equivalents of 3 or 4 with [UI4 (dioxane)2 ] afforded the uranium thioether complex [(AS2 Ph 2 )2 UI2 ] (5 ) and the first example of a uranium‐selenoether complex, [(ASe2 Ph 2 )2 UI2 ] (6 ). X‐ray structures revealed distorted square antiprismatic geometries in which the AE2 Ph 2 ligands are κ 3 ‐coordinated. The nature of the U−ER2 bonding in 5 and 6, as well as methyl‐free analogues of 5 and 6 and a hypothetical ether analogue, was investigated computationally (including NBO, AIM, and ELF calculations) illustrating increasing covalency from O to S to Se. Abstract : Actinide–soft donor linkages are of importance in the context of lanthanide‐actinide separation. The first example of a uranium selenoether complex has been prepared through the use of a rigid SeNSe‐donor pincer ligand. The thioether analogue was also synthesized. Computational studies, including NBO, AIM and ELF calculations, revealed increasing covalency in U−ER2 bonding from O to S to Se.